KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA DITINJAU DARI GAYA KOGNITIF SISWA KELAS VII - Wulandari, Debora Tri; Jamiah, Yulis; Ahmad B.S., Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research is a qualitative research with descriptive method that aims to determine the difficultyof students in solving word problems in terms of cognitive style in algebraic form material. Themain aspect that will be explained in this study is the difficulty of students in completing wordproblems in terms of cognitive style in the form of algebraic material for VII grade students ofJunior High School Negeri 19 Pontianak. The subjects of this study consisted of 4 students of classVII A of Junior High School Negeri 19 Pontianak who had different cognitive styles, namely FieldIndependent and Field Dependent. The results of this study indicate that students who have theField Independent and Field Dependent cognitive styles have difficulty at the stage ofunderstanding problems, planning solutions, solving problems and checking. In addition there arealso several factors that influence students' difficulty in solving story problems in terms of the FieldDependent and Field Independent cognitive styles, namely: Students lack mastering algebraicmaterial, students are less thorough and careful in solving story problems, students do not likemath lessons, students have low motivation in learning mathematics, classrooms that are lessconducive and learning methods applied in the classroom are not appropriate.Keywords: Cognitive Styles, Difficulty, Form of Algebraic